The Central Scandinavian Dolerite Group - Protracted hotspot activity or back-arc magmatism? Constraints from U-Pb baddeleyite geochronology and Hf isotopic data - Söderlund, Ulf; Elming, Sten-Ake; Ernst, Richard; Schissel, Don (Precambrian Research, 2006)
The Central Scandinavian Dolerite Group (CSDG) occurs in five separate complexes in central Sweden and SW Finland. U-Pb baddeleyite ages of dolerite dikes and sills fall into three age intervals: 1264-1271 (the Dalarna complex), 1256-1259 (the Vdsterbotten-Ulvo-Satakunta complexes) and similar to 1247 Ma (the Jamtland complex). Timing and spatial distribution of CSDG are unlike expressions of the voluminous and short-lived magmatism which characterises plume-associated large igneous provinces (LIPs). Protracted mafic magmatism in association with mantle plume tail (hotspot) activity beneath the Fennoscandian lithosphere or discrete events of extension behind an active margin (subduction) are considered more plausible tectonic settings. Both settings are consistent with timing, relative magma volumes between complexes and vertical ascent of individual magma pulses through the crust, as inferred from seismic sections [Korja, A., Heikkinen, P., Aaro, S., 2001. Crustal structure of the northern Baltic Sea palaeorift. Teconophysics 331, 341-358]. In the hotspot model, the lack of a linear track of intrusions can be explained by an almost stationary position of Fermoscandia relative to the hotspot, in agreement with palaeomagnetic data [Elming, S.-angstrom., Mattsson, H., 2001. Post Jotnian basic intrusion in the Fermoscandian Shield, and the break up of Baltica from Laurentia: a palaeomagnetic and AMS study. Precambrian Res. 108, 215-236]). Together with geological evidence, dolerite sill complexes and dike swarms in Labrador (Canada), S Greenland and central Scandinavia in the range 1234-1284 Ma are best explained by long-lived subduction along a continuous Laurentia-Baltica margin preceding Rodinia formation. There is no support for the hypothesis that CSDG was fed by magma derived from a distal mantle plume located between Baltica and Greenland and, hence, for rifting between the cratons at similar to 1.26 Ga. The epsilon-Hf in various members of the CSDG varies between 4.7 and 10.3, which are overall higher than ...